Analysis of Economic Growth at Regional District Sub Province Semarang in the Fiscal Decentralization Era - Amin Pujiati (Universitas Islam Indonesia, 2008)
Every regions government must be able increasing their own regional income. The finance of resources in fiscal decentralization era, such as: regional original income, general allocation funds and natural resources revenue sharing and tax revenue sharingThis research aims to analyze the fiscal decentralization impact to economic growth at regional district in sub province Semarang. The tool of analisis is regression using panel data with Generalized Least Square (GLS) method and Fixed Effect model. It uses district-level data and supplied by the Indonesian Central Bureau of Statistics during 2002 - 2006The regression result shows that regional income, natural resources revenue sharing and tax revenue sharing, and labor forces have positive impact on economic growth at regional district in sub province Semarang. General allocation funds have negative effect towards economic growth at regional district in sub province Semarang. Fiscal decentralization brings more advantages for regions to manage their own fiscal capacities. The regions governments must be have informational advantages concerning resource allocation with optimalKeywords: Fiscal Decentralization, economic growth, Fixed Effect Model